(untitled) (Revista Apotheke, 2025)
This article is the result of a scientific initiation research linked to the project “The Painting Studio as a Laboratory for Teaching and Learning in Visual Arts,” coordinated by Prof. Dr. Jociele Lampert at the State University of Santa Catarina (UDESC). The experimental research explores the possible chromatic variations obtained in the process of producing paints from natural pigments, analyzing physical aspects and color durability. For this study, experiments were conducted using a single organic material: the avocado. Based on the work Art as Experience by John Dewey, the research sought new approaches to problem-solving, emphasizing the integration of theory and practice in the creative process. Additionally, as an extension activity of the Apotheke Painting Studio study group, a workshop was conducted to introduce natural paint-making techniques, offering Visual Arts students at UDESC an alternative methodological approach to creation and artistic practice.